Chemical transformation of Te into new ternary phase PbmCunTem+n nanorods and their surface atom diffusion and optical properties. Issue 56 (24th May 2016) - Wang, Qun; Su, Ziming; Lv, Mingda; Li, Jianhuan; Sun, Baoyu; Zhang, Guangjun
Abstract : The new phase of ternary Pb m Cu n Te m+n was first synthesized using sacrificial template Te. The diffusion of surface atoms was observed upon electron-beam irradiation and their optical band gaps show bigger values than that of PbTe. Abstract : A new stable phase of ternary Pb m Cu n Te m + n with rough surface, including one-dimensional (1D) bamboo-like shaped and curved nanorods with short branches, was first synthesized using Te as a sacrificial template. The structure does not exist in the bulk Cu2 Te–PbTe phase diagram. It is revealed that the optimal Pb 2+ /Cu 2+ chemical reactivity synergistic effect can preserve the initial shape of the Te nanorod parent template, which involves small volume changes and secondary nucleation phenomenon along the entire length of the nanorods. Furthermore, the diffusion of surface atoms and a surface pre-melting on the short branches of the nanorods were observed upon in situ electron-beam irradiation. The average Cu atom diffusion distance calculated (3 × 10 −11 m s −1 ) is higher than the reported value (1.34 × 10 −12 m s −1 ) in Cu2 O at 373 K, which is attributed to the local high temperature created by the incident electron irradiation and large surface to volume ratio of the nanomaterials. In addition, the Pb m Cu n Te m + n nanorods exhibit well-defined and size-dependent optical band gaps ( E g ) in the near-IR region. We envision that the Te template strategy is general and robust and offers easy access to other new phase ternary PbTe-based nanomaterials via carefully balancing the chemical reactivity of the precursor.